2019
DOI: 10.1038/s41598-019-39618-z
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome and plasmid-borne PLacO3O1 promoters differ in sensitivity to critically low temperatures

Abstract: Temperature shifts trigger genome-wide changes in Escherichia coli’s gene expression. We studied if chromosome integration impacts on a gene’s sensitivity to these shifts, by comparing the single-RNA production kinetics of a PLacO3O1 promoter, when chromosomally-integrated and when single-copy plasmid-borne. At suboptimal temperatures their induction range, fold change, and response to decreasing temperatures are similar. At critically low temperatures, the chromosome-integrated promoter becomes weaker and noi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 87 publications
2
6
0
Order By: Relevance
“…In agreement, a recent study [Oliveira et al, 2019] tracked RNA production at the molecular level by synthetic variants of the Lac promoter. It was shown that, at low temperatures, RNA production kinetics is weaker and noisier when the gene is chromosome integrated than when it is plasmid borne (in plasmids, supercoiling buildup should be much slower due to the annihilation of positive and negative supercoils [Liu et al, 1987]).…”
Section: Introductionsupporting
confidence: 78%
See 3 more Smart Citations
“…In agreement, a recent study [Oliveira et al, 2019] tracked RNA production at the molecular level by synthetic variants of the Lac promoter. It was shown that, at low temperatures, RNA production kinetics is weaker and noisier when the gene is chromosome integrated than when it is plasmid borne (in plasmids, supercoiling buildup should be much slower due to the annihilation of positive and negative supercoils [Liu et al, 1987]).…”
Section: Introductionsupporting
confidence: 78%
“…To our knowledge, temperature sensitive PSB is the first identified physical mechanism of how an E. coli gene can be CS responsive, and evidence suggests that it is present in nearly half of E. coli ’s CSR genes. This finding, first hypothesized in [Oliveira et al, 2019], opens an avenue for the engineering of future synthetic, temperature sensitive and temperature resistant gene regulatory circuits, whose functioning could be tuned by the adaptive regulation of Gyrase activity. Further, we expect that it will contribute to learning how the short- and long-term transcriptional programs of E. coli responsive to CS have evolved.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This diversity of single-gene responses may be explained by the likely existence of multiple causes for their alterations in expression rates during cold shock. For example, studies using synthetic gene constructs suggest that temperature can affect the kinetics of rate-limiting steps in transcription initiation, such as the closed and open complex formations (4), and such effects can differ between promoters (16). Other studies showed that temperature affects chromosomal DNA compaction (17)(18)(19), which is associated with supercoiling buildup (19,20).…”
Section: Introductionmentioning
confidence: 99%